The tectonic stress field and modern movements in the Earth’s crust in the Southeast continental Shelf of Vietnam - Hưng, Dương Quốc; Thanh, Bùi Nhị; Lương, Nguyễn Văn; Điệp, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2013)
In this paper, the tectonic stress field in the Southeast Continental Shelf of Vietnam region has established on the base of seismic focal mechanism, volcanic and borehole geophysic data. It is shown that, the tectonic stress field of study region complicatedly changes in the space. In the West region, the stress field of lateral strike-normal dip slip pattern with the NNW-SSE maximum compressive direction is predominant. This stress field reactivates sub-longitudinal faults in the left lateral strike - normal dip slip active mechanism, concurrently, creates the strike-slip displacement components in the modern movements of NW-SE and NE-SE faults. Predominant in the East region is the tectonic stress field of the normal-lateral slip or pure normal dip-slip patterns with the maximum tensional stresses changing from the WNW-ESE in the Mang Cau - Phu Quy and KT.109° fault zones to NW-SE direction in the Northeast Nam Con Son basin. This stress field reactivates sub-longitudinal and NE-SW faults, respectively, in the normal-right lateral slip and normal dip-slip active mechanisms.